2007
DOI: 10.1021/jf071349+
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Antioxidant Activities of Natural Vanilla Extract and Its Constituent Compounds throughin VitroModels

Abstract: Vanilla extract was prepared by extraction of cured vanilla beans with aqueous ethyl alcohol (60%). The extract was profiled by HPLC, wherein major compounds, viz., vanillic acid, 4-hydroxybenzyl alcohol, 4-hydroxy-3-methoxybenzyl alcohol, 4-hydroxybenzaldehyde and vanillin, could be identified and separated. Extract and pure standard compounds were screened for antioxidant activity using beta-carotene-linoleate and DPPH in vitro model systems. At a concentration of 200 ppm, the extract showed 26% and 43% of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 20 publications
9
47
0
1
Order By: Relevance
“…The order of relaxing potencies of VA and its analogs may be related to their varying hydrophobicity which, to judge from the elution time during reversed-phase high-performance liquid chromatography separation (Shyamala et al, 2007;Tai et al, 2011), follows the same ranking as observed in the present experiments. Such a difference in hydrophobicity of VA, VAA, and EtVA may be responsible not only for their different antioxidant activities/capacities (Tai et al, 2011) but also for their varying potencies in inhibiting L-type Ca 21 channels (as discussed herein), which are involved in contractions to KCl, U46619, and endothelin-1 Kasuya et al, 1989;Sato et al, 2000;Nobe and Paul, 2001).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The order of relaxing potencies of VA and its analogs may be related to their varying hydrophobicity which, to judge from the elution time during reversed-phase high-performance liquid chromatography separation (Shyamala et al, 2007;Tai et al, 2011), follows the same ranking as observed in the present experiments. Such a difference in hydrophobicity of VA, VAA, and EtVA may be responsible not only for their different antioxidant activities/capacities (Tai et al, 2011) but also for their varying potencies in inhibiting L-type Ca 21 channels (as discussed herein), which are involved in contractions to KCl, U46619, and endothelin-1 Kasuya et al, 1989;Sato et al, 2000;Nobe and Paul, 2001).…”
Section: Discussionsupporting
confidence: 73%
“…Based on these properties, VA, VAA, and EtVA could be used to prevent or relieve exaggerated Ca 21 influx resulting in PKC activation in coronary (Ito et al, 1994;Kadokami, et al, 1996) or cerebral (Laher and Zhang, 2001) vasospasm and other cardiovascular disorders (Khalil, 2013). However, the concentrations of VA and its analogs needed to act as antioxidants (Shyamala et al, 2007;Jung et al, 2010;Kwon et al, 2013;Lee et al, 2013) or as vasodilators (present study) are larger than the measured plasma level [0.0005 mM] reached after oral administration of 30 mg/kg VA in male ICR (imprinting control region) mice (Tai et al, 2011). This comparison implies that to obtain a therapeutically favorable coronary and/or cerebral vasodilator, larger doses of VA and its analogs would be required than are achieved with their use as additives.…”
Section: Coronary and Basilar Arterial Relaxations To Vanillinmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that vanillyl alcohol and vanillic acid exerted antioxidant activity. 25) Ethyl vanillin and apocynin reacted with ABTS þ in a manner similar to that of vanillin. estimated that 1 mole of ethyl vanillin and apocynin scavenged 2.5 moles of ABTS þ in reaction over 120 min, although one molecule of ethyl vanillin and apocynin has only one oxidizable phenolic hydroxyl group.…”
Section: Abtsmentioning
confidence: 99%